Magnetic Resonance Imaging of Clubfoot Treated With the Ponseti Method: A Short-Term Outcome Study - Zhang, Jiangchao; Wang, Ningqing; Lv, Haixiang; Liu, Zhenjiang (Frontiers in Pediatrics, 2022)
Objective: To quantitatively evaluate the effectiveness of the Ponseti method for the correction of clubfoot, we decided to use Magnetic resonance imaging to evaluate changes in the tarsal bones relationship. Methods: This is a retrospective study of fifteen children with clubfoot treated with Ponseti method. MRI studies were obtained using a 3.0T machine(GE, America). T1-weighted and T2-weighted images were acquired in the standard anatomic sagittal, transverse, and coronal planes. For the measurement, the best slice that clearly demonstrated the anatomy was chosen. Sagittal talocalcaneal angle, sagittal tibiocalcaneal angle, coronal tibiocalcaneal angle, transverse talar neck angle, transverse talonavicular angle and transverse talocalcaneal angle were measured. The eighteen corrected clubfoot were compared with the twelve unilateral normal feet at clinical and radiological levels using a Pirani scoring system and MRI, respectively. Results: Fifteen cases (twelve boys, three girls) with clubfoot were examined by using MRI. Twelve cases had unilateral and three had bilateral involvement(eleven left clubfoot, seven right clubfoot), giving a total of eighteen clubfoot compared with twelve normal feet. The mean age of patients at examination was 47.7months (8-96 months). The recovery of the corrected clubfoot in these patients met the goals of Ponseti treatment(functional, normal looking, pain-free, plantigrade foot). Before Ponseti treatment, the mean Pirani score of clubfoot was 5.5(5-6). During this follow-up, the Pirani score was 0.07(0-0.05). The results of MRI indicated that only the transverse talonavicular angle showed significant difference between the treated clubfoot and the normal feet(P< 0.001). One case had dorsal talonavicular subluxation in sagittal plane and had lateral subluxation of the navicular in transverse plane, which have never been reported in previous studies. Conclusions: Although the appearance and function of clubfoot recovered well after the Ponseti method, the results of MRI indicated that Ponseti method successfully corrected the varus, cavus, and equinus deformities and incompletely corrected the adduction deformity regarding transverse talonavicular angle. At the same time, the Ponseti method may cause dorsal talonavicular subluxation in sagittal plane and lateral subluxation of the navicular in transverse plane on MRI.